Effect of gypsum crystallization characteristics on fine particle emission after desulfurization. Issue 4 (16th May 2017) - Pan, Danping; Wu, Hao; Yang, Linjun
Abstract: For the control of fine particle emission after desulfurization, the effect of gypsum crystallization characteristics during limestone‐gypsum wet flue gas desulfurization process was investigated. The results showed that crystals produced during the desulfurization process were mostly CaSO4 · 2H2 O with uniform prismatic shape. An optimal temperature, lower pH value and the adoption of forced oxidation were beneficial to restrain the generation of fine crystals in the desulfurization slurry. Meanwhile, the optimization of the desulfurization environment was essential for the improvement of the gypsum crystal qualities. Furthermore, the fine particle concentrations after desulfurization were related to the gypsum crystallization characteristics in the slurry, which were decreased by 20%–30% with optimized slurry as the generation of fine crystals in the desulfurization slurry was inhibited. Hence, the optimization of gypsum crystallization characteristics in the slurry was a feasible method to reduce the fine particle emissions after desulfurization. © 2017 Curtin University of Technology and John Wiley & Sons, Ltd.